PEMBERIAN PGPR (Plant Growth Promoting Rhizobacteria) DENGAN KONSENTRASI YANG BERBEDA PADA PERTUMBUHAN BENIH TEBU (Saccharum Officinarum L.) ASAL BUD SET - Raudatul Jannah (Unit Penelitian dan Pengabdian Masyarakat (UP2M) Politeknik Banjarnegara, 2022)
Sugarcane (Saccharum officinarum L.) is a plantation crop that has an important role in improving the economy in Indonesia as well as the main raw material in sugar production. The single bud planting method is a nursery method that is widely used and in demand by farmers today for the production of sugarcane seeds. One of the best ways to grow seedlings is to have a good root system to get optimal nutrients. One of the efforts to support the growth and function of the roots is by giving PGPR (Plant Growth Promoting Rhizobacteria). This study aims to determine the effect of differences in PGPR concentration on the growth of sugarcane bud set seedlings. The research was carried out from April to June 2021 at the LPP Polytechnic Integrated Practice Garden, Wedomartani, Sleman, Yogyakarta. This study used a non-factorial Randomized Block Design (RAK) method on one PGPR factor with 6 different concentration treatments. Each treatment was repeated 3 times so that there were 54 experimental units. The treatments used were PGPR concentrations of 0.3 ml/polybag, 0.6 mL/polybag, 0.9 mL/polybag, 1.2 mL/polybag and 1.5 mL/polybag. The results showed that the administration of PGPR with different concentrations did not significantly affect all parameters of sugarcane seedlings from the bud set observed, namely: plant height, number of leaves, stem diameter and root length.